Trawling and creeling for nephrops: impacts on biodiversity and populations structure - Marques, Lino Alexandre António (2016)
Dissertação de mestrado, Aquacultura e Pescas, Faculdade de Ciências e Tecnologia, Universidade do Algarve, 2015